Elucidation of α-glucosidase inhibitory activity and UHPLC-ESI-QTOF-MS based metabolic profiling of endophytic fungi Alternaria alternata BRN05 isolated from seeds of Swietenia macrophylla king - Kumar, Piyush; Kannakazhi Kantari, Sai Anand; Biswal, Ranendra Pratap; Ghanta, Prasanth; Dharanikota, Malleswara (Frontiers in Fungal Biology, 2025)
There is a growing demand for new diabetes drugs with fewer side effects to replace current medications known for their adverse effects. Inhibition of α-glucosidase responsible for postprandial hyperglycemia among diabetes patients is a promising strategy for managing the disease. This study aims to explore and identify novel bioactive metabolites with anti-diabetes potential from Alternaria alternata BRN05, an endophytic fungus isolated from a well-known medicinal plant Swietenia macrophylla King. Ethyl acetate extracts of Alternaria alternata BRN05 grown in full-strength (EFS) and quarter-strength (EQS) media, respectively were evaluated for their α-glucosidase inhibitory activities. Based on IC50 values, EQS exhibited significantly greater inhibitory activity (0.01482 ± 1.809 mg/mL) as compared to EFS (1.16 ± 0.173 mg/mL) as well as acarbose control (0.494 ± 0.009 mg/mL). EFS and EQS were subjected to metabolic profiling using Ultra-High-Performance Liquid Chromatography - Electrospray Ionization - Quadrupole Time-of-Flight Mass Spectrometry (UHPLC-ESI-QTOF-MS). A total of nineteen metabolites from EFS and twenty from EQS were tentatively identified based on MS/MS fragmentation. Molecular docking analysis revealed that twelve among these exhibited greater binding energies than that of acarbose (-6.6 kcal/mol). Molecular Dynamics (MD) simulations of 3’,4’,7-trihydroxyisoflavanone (THF) and alternariol 9-methyl ether (AME) from EQS, exhibiting high binding energies (-7.5 and -7 kcal/mol, respectively), were performed to investigate their interactions with human intestinal α-glucosidase. Results suggest THF possesses strong inhibitory potential, making it a promising candidate for diabetes management.